2018
DOI: 10.1016/j.micpath.2017.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Neoteric advancement in TB drugs and an overview on the anti-tubercular role of peptides through computational approaches

Abstract: Tuberculosis (TB) is a devastating threat to human health whose treatment without the emergence of drug resistant Mycobacterium tuberculosis (M. tuberculosis) is the million-dollar question at present. The pathogenesis of M. tuberculosis has been extensively studied which represents unique defence strategies by infecting macrophages. Several anti-tubercular drugs with varied mode of action and administration from diversified sources have been used for the treatment of TB that later contributed to the emergence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Usually, small molecule compounds or peptides are selected to increase toxin activity because they act as inhibitors of TA interactions. Peptides obtained from various sources have already been investigated for their ability to act as antibacterial agents and to replace existing antibiotics [84,85]. In most cases, toxins do not exhibit toxicity when they are part of a TA complex because the antitoxin completely blocks the active site of the toxin.…”
Section: Application Of Antimicrobial Peptides Based On the Type Imentioning
confidence: 99%
“…Usually, small molecule compounds or peptides are selected to increase toxin activity because they act as inhibitors of TA interactions. Peptides obtained from various sources have already been investigated for their ability to act as antibacterial agents and to replace existing antibiotics [84,85]. In most cases, toxins do not exhibit toxicity when they are part of a TA complex because the antitoxin completely blocks the active site of the toxin.…”
Section: Application Of Antimicrobial Peptides Based On the Type Imentioning
confidence: 99%
“…One of the most influential characteristics of peptides is their pleiotropic effects towards a wide range of biological targets, thus making them better drug candidates with lower toxicity than that of small molecules. Several studies have shown the anti-tubercular properties of peptides and their unique mechanism of actions, suggesting that they are an ideal approach for TB management [5]. Peptides derived from human immune and non-immune cells, venom, fungi, bacteria, and several other sources have been shown to act as effective anti-tubercular agents [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the experimental identification and development of AtbPs is time-consuming and expensive. To assist and expedite the discovery of AtbPs, in silico methods are needed prior to their synthesis [5]. A trending computational method, machine learning (ML), could provide an excellent platform for the prediction and design of AtbPs.…”
Section: Introductionmentioning
confidence: 99%
“…TB can infect any part of the body although disease manifestation is generally observed in the lungs. Apart from pulmonary TB, extra-pulmonary TB is mainly found in immunocompromised individuals which includes osseous tuberculosis found in the bones and tuberculous ulcer occurring on the skin 8 .…”
Section: Tb Etiology and Global Tb Crisismentioning
confidence: 99%
“…The innermost layer is a typical phospholipid bilayer plasma membrane (PM), then a peptidoglycan (PG) layer provides a sacculus support to the plasma membrane and it is linked externally to a layer of arabinoglactan (AG). Via the mycoloyl residues (mycolic acids), this covalent PG-AG complex is linked to the outer membrane Synthesis of cell wall is mediated by the mycolyl transferases, namely the antigen-85 protein complexes 8 . These transferases catalyse the transfer of mycolic acid in the cytosolic compartment from TMM to form TDM and a free trehalose.…”
Section: Mycobacterial Cell Envelopementioning
confidence: 99%